Proposed new interior design scheme of showroom for Bentley Sdn. Bhd. at Jalan Autocity, Juru, Off Penang / Muhammad Harifi Herry Hermawan - Herry Hermawan, Muhammad Harifi (Faculty of Architecture, Planning and Surveying, 2012)
This project is about Proposed Interior New Interior Design Scheme of Showroom of Bentley at Autocity, Juru,Penang.Bentley Motors are new high luxury car brand since 1931. Bentley Motors just opened their showroom only six ear,2006.The client of this project is their marketing and PR manager,Mr. Andrew Wong.The reason to proposed this project is because the client decided to widen its business outside Kuala Lumpur, preferably those of tourist attraction cities especially north Malaysia like Juru, Penang.Juru was choose after had done survey and it seems that site is suitable for this project.The objective is to create a very well Showroom with comfort and style with a good price related and attract more customers either from north Malaysia to the area has been chosen..With this project,north Malaysians do not have to come to Kuala Lumpur to see the new luxury car brand, Bentley. The target market for the customers of this showroom is for Malaysians who live at north Malaysia.